Understanding the relationship between environmental management accounting and firm performance : The role of environmental innovation and stakeholder integration – Evidence from a developing country - Gerged, Ali Meftah; Zahoor, Nadia; Cowton, Christopher J. (Elsevier, 2023)
This study examines the role of environmental management accounting (EMA) as a mechanism for enhancing firm performance. Primary data were collected by means of a questionnaire survey of chief executive officers and finance managers of SMEs in Pakistan. Analysis of the responses received from 204 firms confirms a significant direct relationship between EMA and firm performance. We find that this effect is attributable to the mediating impact of environmental innovation. Our findings also suggest that stakeholder integration positively moderates the association between environmental innovation and firm performance, and so leverages the impact of EMA. The findings are robust to several checks and are further explored at the level of the individual dimensions of some of the constructs used. Thus, we contribute novel evidence regarding the relationship between EMA and firm performance, in the form of both environmental and financial performance. The findings offer practical implications for managers and accountants, and we make several suggestions for future research that could build on our study.
Keywords: Developing economy; Environmental innovation; Environmental management accounting; Pakistan; Stakeholder integration; small and medium-sized enterprises